Pengaruh Pendidikan dan Pelatihan (Diklat) terhadap Kinerja Pegawai di Dinas Pendidikan Kebudayaan Provinsi Gorontalo - Zulpani Alimudin; Rustam Tohopi; Romy Tantu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to determine the influence of Diklat on employee performance at the Department of Education and Culture of Gorontalo Province. The sample in this study consisted of 58 respondents. The data used in this research were primary. Data collection was conducted through the distribution of questionnaires. The data analysis technique employed was simple linear regression. The results of this study indicate that Diklat have a positive and significant influence on employee performance at the Department of Education and Culture of Gorontalo Province, with a coefficient of determination of 66.90%, while the remaining 33.10% is influenced by other variables not examined in this study, such as organizational culture, work environment, leadership, career management, work commitment, work supervision, and information technology within the organization. The positive test results imply that the improvement in employee performance at the Department of Education and Culture of Gorontalo Province occurs due to intensive Diklat that align with the needs of human resource development in public sector organizations.